Altruism and tax compliance: Unveiling the dual role of charitable giving and social norms in global tax evasion - Ramadhan, Muhammad Rheza; Widiarto, Fajar; Liriyansah, Bismar; Khusaini, Fachrul; Arifandi, Budi (WIM Solusi Prima, 2025)
This study investigates the relationship between altruistic behaviors and tax evasion, using panel data from 172 countries spanning 2011 to 2020. The analysis focuses on three dimensions of altruism—helping strangers, volunteering, and donating to charity—derived from the World Giving Index, while tax evasion is proxied by the size of the informal economy as estimated by the IMF. With a final sample of 1,103 country-year observations, the study employs a fixed effects regression model to account for unobserved, time-invariant heterogeneity across countries and global shocks over time. GDP per capita, sourced from the World Bank, is included as a control variable. The findings reveal a dual relationship: the percentage of individuals helping strangers is negatively correlated with tax evasion, suggesting that strong social norms and intrinsic motivations for altruistic behavior promote tax compliance. In contrast, the percentage of individuals donating to charity is positively correlated with tax evasion, indicating that charitable giving may sometimes rationalize non-compliance through mechanisms like the Crowding-Out Hypothesis or the Compensatory Altruism Hypothesis. Volunteering, however, shows no significant effect on tax evasion. These results underscore the complexity of the relationship between pro-social behaviors and tax compliance. Policymakers are encouraged to promote social norms that foster both altruism and tax compliance while carefully designing tax incentives for charitable giving to prevent unintended consequences. This study contributes to the literature by providing nuanced insights into the interplay between altruistic behaviors and tax evasion on a global scale, highlighting the importance of context in understanding compliance behaviors.